'None of my ancestors ever discussed this disease before!' How disease information shapes adaptive capacity of marginalised rural populations in India. - Festus A Asaaga; Mujeeb Rahman; Suresh D Kalegowda; Jagadeesh Mathapati; Irfanahemad Savanur; Prashanth N Srinivas; Tanya Seshadri; Darshan Narayanswamy; Shivani K Kiran; Meera A Oommen; Juliette C Young; Bethan V Purse (Public Library of Science (PLoS), 2021)
Smallholder farmer and tribal communities are often characterised as marginalised and highly vulnerable to emerging zoonotic diseases due to their relatively poor access to healthcare, worse-off health outcomes, proximity to sources of disease risks, and their social and livelihood organisation. Yet, access to relevant and timely disease information that could strengthen their adaptive capacity remain challenging and poorly characterised in the empirical literature. This paper addresses this gap by exploring the role of disease information in shaping the adaptive capacity of smallholder farmer and tribal groups to Kyasanur Forest Disease (KFD), a tick-borne viral haemorrhagic fever. We carried out household surveys (n = 229) and in-depth interviews (n = 25) in two affected districts-Shimoga and Wayanad-in the Western Ghats region. Our findings suggest that, despite the generally limited awareness about KFD, access to disease information improved households' propensity to implement adaptation strategies relative to households that had no access to it. Of the variety of adaptation strategies implemented, vaccination, avoiding forest visits, wearing of protective clothing and footwear, application of dimethyl phthalate (DMP) oil and income diversification were identified by respondents as important adaptive measures during the outbreak seasons. Even so, we identified significant differences between individuals in exposure to disease information and its contribution to substantive adaptive action. Households reported several barriers to implement adaptation strategies including, lack of disease information, low efficacy of existing vaccine, distrust, religio-cultural sentiments, and livelihood concerns. We also found that informal information sharing presented a promising avenue from a health extension perspective albeit with trade-offs with potential distortion of the messages through misinformation and/or reporting bias. Altogether, our findings stress the importance of contextualising disease information and implementing interventions in a participatory way that sufficiently addresses the social determinants of health in order to bolster households' adaptive capacity to KFD and other neglected endemic zoonoses.